Enhancing the Tourism Industry in the Post-Pandemic Era: Through Leveraging the Effect of China’s Digital Fiat Currency - Lyu, Wenbo; Xu, Qianwan (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
After the COVID-19 epidemic, the global tourism industry has suffered a huge blow and has entered a long road to recovery. This study sought to investigate the impact of digital yuan (e-CNY) in driving consumption. By constructing a regression model using data related to consumer power, this paper examines the effect of digital RMB in promoting consumption. The findings indicate that the development of digital RMB has a positive influence on boosting consumption, effectively enhancing the purchasing power of Chinese residents, and facilitating high-quality economic growth in China. This study seeks to analyze the factors influencing consumption promotion through the use of digital RMB in the market application and propose targeted improvement measures based on the significance of these factors. This will help promote more effective utilization of digital RMB, cater to a broader user base, and steadily advance its development process. Starting from the concept of system design, the article designs the characteristics, methods, circulation methods and leverage of Singapore's digital legal currency in detail, quantifies the economic index of Singapore's tourism industry, and obtains reliable policy suggestions. Finally, the article conducts empirical data analysis from the perspective of China's digital renminbi, proves the promotion effect of digital legal currency with facts, and gives corresponding suggestions to government departments.